Modeling of nitrogen and sediment transport in Nagura River, Ishigaki City and That Luang wetlands, Vientiane City - Khamfeuane Sioudom
This study presents the results of applying the Soil and Water Assessment Tool (SWAT) model to model of nitrogen and sediment transport in Nagura River, Ishigaki City, Okinawa, Japan and That Luang wetlands, Vientiane City, Lao P.D.R., obtained by two research groups, namely, one based in Ishigaki City, Okinawa, Japan, and the other in the Vientiane City, Lao P.D.R. SWAT models water nutrients and sediment transport in rivers swamp and wetlands. Input data requirement are:1. Climate data (daily rainfall, max. and min. temperature, solar radiation, relative humility and wind speed) 2. Land cover and soil classes. 3. Topography (DEM). Point sources of nutrients. 5. Management practices for fertilizer application. The long term continuous hydrologic simulations were evaluated by comparing simulated daily and monthly average stream flows with daily and monthly observed stream flows at a set evenly distributed gauging stations. SWAT was applied to simulate hydrology, sediment and nutrient in Ishigaki City watershed, situated in Nagura River basin and Vientiane City watershed, situated in the Vientiane stream network system basin. The results herein are the "first-cut" preliminary analyses. For Ishigaki City, the following statistics were computed for flow simulations: (1) mean square error method (SSQ), expressed as a percent error bias (PBIAS), (2) Nash-Sutcliffe coefficient of efficiency (NSE), for values in a single year, first cumulatively for a one-year calibration period from day 1 to 365 for the year 2006, and then cumulatively for the entire one year simulation from this time series period for 2006. Model simulations of sediment transport were assessed by comparing graphical results of measured versus simulated constituent concentrations. A comparison of daily measured concentration versus simulated daily average suspended sediment concentration for the simulation period from day 1 to 365 for 2006 was made. For simulation at the drainage outlet, the SSQ of total average water flow was 0.14 m 3/s, which was caused by an underestimation of measured surface flow.The PBIAS value of -38.77% was computed for the watershed outlet in Kannda station westward of Ishigaki City, indicating a bias toward moderate overestimation. NSE was computed to be 0.53. Given that the NSE value is between 0.75 and 0.36, the simulation results are considered to be good. The overall evaluation of the SWAT model indicates that the model has the capability of fairly predicting surface runoff flow and sediment concentration for different soil. land use, s;opes and weather conditions. For Vientiane City, the following statistics for dimulated values of stream flow for a single year were computed : (1) mean square error method (SSG), expressed as a percent error bias (PBIAS), and (2) Nash-Sutcliffe coefficient of eefficiency. Simulated mpnthly stream flows were compared with observed month stream flows at five evenly distributed gauging stations; comulatively for a one-year simulation period from month Jan-2007 to Dec.-2007. Simulated monthly nitrate-nitrogen concentrations (NO3-N) were compared with observed monthly nutrient loads at one outlet watershed gauging station at Vientiane. However, for Vientiane there were numbers of scenarios involving different nutrient spatial and point source. The foloowing statistics were computed; (1) mean square error method (SSQ), expressed as a percent error bias (PBIAS) (2) Nash-Sutcliffe coefficient of efficiency, cumulatively overtake five-year calibration period starting from Jan-2000 to Dec.- 2004 (one year for flow). The same scenarios (P1, F1 and U1) were used for NH4-N loading simulation. Simulated monthly nitrogen concentrations (NH4-N) were compared with observed monthly nutrient loads at one evenly distributed outlet watershed gauging station. The SSQ of the scenarios for NH4-N loading was satisfactory whereas for PBIAS, only case P1 exhibited acceptable values. The other scenario over estimated ammonia loading. As for NSE, all scenarios displayed negative values. Fpr scenario 1 wherein the average daily precipitation for 2007 was used the model simulated accurately the observed flows for the simulation period for all the stations except Houakhua. The same can be said about the second scenario (20% higher rainfall), where only Houakhoau exhibited poor prediction for flow. And for scenario 3 (20% less rainfall), only one station predicted fairly accurate flows while stations the remaining three hust had satisfactory estimated flow. The Houakhoua station failed to have acceptable monthly flows for at any hence and for every scenario 2007. Only the scenarion with PO (no point source), FO (no fertilizer management practices) and UO (no residential high density) predicted NO3-N loading accurately with a SSQ value of 0.83 m3/s, PBIAS of 3.56% and NSE value of -0.19. The other thre scenarios namely there is only the point source (scenario 2, P1=point source), only the fertilizer application (scenarion 3, F1=fertilizer management practices) and there is only residential high density (scenario 4, U1= residential high density)exhibited more than 6 m3/s for SSQ and more than 150% PBIAS which indicate overestimation with respect to the observed values. They also showed fairly high negative NSE.